2020
DOI: 10.1111/ppl.13190
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 modifies responses to water‐stress and flowering of Mediterranean desert truffle mycorrhizal shrubs

Abstract: Predicted increases in atmospheric concentration of carbon dioxide (CO 2) coupled with increased temperatures and drought are expected to strongly influence the development of most of the plant species in the world, especially in areas with high risk of desertification like the Mediterranean basin. Helianthemum almeriense is an ecologically important Mediterranean shrub with an added interest because it serves as the host for the Terfezia claveryi mycorrhizal fungus, which is a desert truffle with increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Desert truffle plants confirmed a very clear phenology along the year with different milestones in autumn, winter, spring, and summer according to the results of this work (Table 1 ) and as previously reported by Andrino et al ( 2019 ) and Marqués-Gálvez et al ( 2020a , b ). Although Andrino et al ( 2019 ) showed that all plant and fungal changes and developments, from summer to spring, should be crucial for proper fruiting and crop yield, they also confirmed the experience of some gatherers and farmers, related to the importance of the two key periods: autumn and spring.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Desert truffle plants confirmed a very clear phenology along the year with different milestones in autumn, winter, spring, and summer according to the results of this work (Table 1 ) and as previously reported by Andrino et al ( 2019 ) and Marqués-Gálvez et al ( 2020a , b ). Although Andrino et al ( 2019 ) showed that all plant and fungal changes and developments, from summer to spring, should be crucial for proper fruiting and crop yield, they also confirmed the experience of some gatherers and farmers, related to the importance of the two key periods: autumn and spring.…”
Section: Discussionsupporting
confidence: 91%
“…But in this work, the high presence of P-solubilizing bacteria was not related to high photosynthesis values in spring (Table 1 ). Indeed, the photosynthesis in spring, according to Marqués-Gálvez et al ( 2020a , b ), was already close to its minimum due to the limitation by VPD and/or drought. In spring, the fungal partner, however, produces its fruiting bodies (Table 1 ) and high metabolic activity should occur belowground, justifying a higher demand of nutrients.…”
Section: Discussionmentioning
confidence: 90%
“…The greater vertical decoupling of water and nutrient availability in soil/bedrock profiles under warming could decrease or offset the projected increases in plant photosynthesis and WUE in response to rising atmospheric CO 2 concentration (Swann et al, 2016;Peñuelas et al, 2017Peñuelas et al, , 2020Marqu es-G alvez et al, 2020) through increases in nutritional limitation of carbon assimilation. Negative impacts could be expected even in nondryland ecosystems with irregular rainfall distribution and frequent occurrence of long rainless periods, in which warming-induced increases in evapotranspiration and accelerated topsoil drying (Berg et al, 2017) could also lead to longer and more frequent periods of spatial decoupling between topsoil nutrients and subsoil/bedrock water availability.…”
Section: Shoot Biomass Production and Survivalmentioning
confidence: 99%
“…Helianthemum species serve as hosts of ectomycorrhizal fungi ( Terfezia sp., Picoa sp.) that produce desert truffles of high commercial value (Marqués‐Gálvez et al ., 2020). Maximum rooting depth in this shrub species is 65–100 cm (Guerrero‐Campo et al ., 2006; Palacio et al ., 2017), which makes it suitable for evaluating potential changes in soil resource utilization in response to climate manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the area cultivated with the desert truffle T. claveryi has been increased in semiarid areas of Spain [ 5 , 13 ], becoming an alternative agricultural crop thanks to low water requirements for cultivation [ 14 ]. Until now, some abiotic factors or agroclimatic parameters associated with plant management and the control of fungal fruiting have been studied [ 14 , 15 , 16 ]. Although this knowledge on mycorrhizal plant phenology could helped to stabilise annual fluctuations in yield ascocarps production [ 17 ], there are still high fluctuations within the same plantation, resulting in productive and non-productive areas or “patches” [ 18 ].…”
Section: Introductionmentioning
confidence: 99%